Evaluation of the modified FINDRISC to identify individuals at high risk for diabetes among middle‐aged white and black ARIC study participants. Issue 9 (22nd May 2017) - Kulkarni, Manjusha; Foraker, Randi E.; McNeill, Ann M.; Girman, Cynthia; Golden, Sherita H.; Rosamond, Wayne D.; Duncan, Bruce; Schmidt, Maria Ines; Tuomilehto, Jaakko
Abstract : Objective: To evaluate a modified Finnish Diabetes Risk Score (FINDRISC) for predicting the risk of incident diabetes among white and black middle‐aged participants from the Atherosclerosis Risk in Communities (ARIC) study. Research design and methods: We assessed 9754 ARIC cohort participants who were free of diabetes at baseline. Logistic regression and receiver operator characteristic (ROC) curves were used to evaluate a modified FINDRISC for predicting incident diabetes after 9 years of follow‐up, overall and by race/gender group. The modified FINDRISC used comprised age, body mass index, waist circumference, blood pressure medication and family history. Results: The mean FINDRISC (range, 2 [lowest risk] to 17 [highest risk]) for black women was higher (9.9 ± 3.6) than that for black men (7.6 ± 3.9), white women (8.0 ± 3.6) and white men (7.6 ± 3.5). The incidence of diabetes increased generally across deciles of FINDRISC for all 4 race/gender groups. ROC curve statistics for the FINDRISC showed the highest area under the curve for white women (0.77) and the lowest for black men (0.70). Conclusions: We used a modified FINDRISC to predict the 9‐year risk of incident diabetes in a biracial US population. The modified risk score can be useful for early screening of incident diabetes in biracial populations, which may be helpful for early interventions to delay or prevent diabetes.